Free flow electrophoresis separation and AMS quantitation of (14)C-naphthalene-protein adducts - Buchholz, Bruce A. (2010)
Naphthalene is a volatile aromatic hydrocarbon to which humans are exposed from a variety of sources including mobile air sources and cigarette smoke. Naphthalene produces dose- (concentration) dependent injury to airway epithelial cells of murine lung which is observed at concentrations well below the current occupational exposure standard. Toxicity is dependent upon the cytochrome P450 mediated metabolic activation of the parent substrate to unstable metabolites which become bound covalently to tissue proteins. Nearly 70 proteins have been identified as forming adducts with reactive naphthalene metabolites using in vitro systems but very little work has been conducted in vivo because reasonably large amounts (100 μCi) of (14)C labeled parent compound must be administered to generate detectable adduct levels on storage phosphor screens following separation of labeled proteins by 2 D gel electrophoresis. The work described here was done to provide proof of concept that protein separation by free flow electrophoresis followed by AMS detection of protein fractions containing protein bound reactive metabolites would provide adducted protein profiles in animals dosed with trace quantities of labeled naphthalene. Mice were administered 200 mg/kg naphthalene intraperitoneally at a calculated specific activity of 2 DPM/nmol (1 pCi/nmol) and respiratory epithelial tissue was obtained by lysis lavage 4 hr post injection. Free flow electrophoresis (FFE) separates proteins in the liquid phase over a large pH range (2.5–11.5) using low molecular weight acids and bases to modify the pH. The apparatus separates fractions into standard 96-well plates that can be used in other protein analysis techniques. The buffers of the fractions have very high carbon content, however, and need to be dialyzed to yield buffers compatible with (14)C-AMS. We describe the processing techniques required to couple FFE to AMS for quantitation of protein adducts.